Tackling terrorist content online - Propaganda and content moderation - Stuart Macdonald (2023)
This report was produced as part of the EU-funded Tech Against Terrorism Europe project. Its aims to provide an overview of the response of the tech industry to online terrorist and violent extremist content. The report begins with some contextual background, describing the diverse range of online services utilised by terrorists and extremists and the process by which propaganda is disseminated online. The second part details industry responses. As well as referrals from users and law enforcement, it describes the use of AI for proactive detection and collaborative, cross-platform initiatives. The final part describes four wider policy issues: transparency; definitional clarity; the impact on those targeted; and, the use of online data for predictive purposes. The report concludes with a set of six recommendations.